Unequal development in Barcelos, Northwest Portugal: articulation of the central-peripheral model with the territorialist model - Cardoso, Antonio; Universidad de Minho Portugal (Editorial Javeriana., 2015)
In the context of Minho´s regional dynamics, some statistical indicators highlight serious socio-spatial and socio-economic disparities, not only between social groups, but also between sectors (agriculture, industry and services) and socio-spatial areas with different levels of (under)development.From the historical-sociological perspective, this study briefly describes socio-demographic change in the northern region, more specifically in the municipality of Barcelos. Territorial imbalances were detected in comparing more central municipalities with those of the interior. Besides this, the aim is to detect other dimensions of social inequality such as infrastructure, unemployment, and health; social security and housing, on the one hand, and culture and education on the other. Despite some improvements in infrastructure and facilities, the Minho region is permeated by social, educational and cultural disparities. This assymetrical situation reproduces at the regional and local level an unequal national distribution of health, education and cultural resources. In the current context of globalisation, these indicate the analytical importance of the centre-peripheral theory, not only at the global economy level, but also at the national and regional levels.